2019
DOI: 10.1186/s12936-019-2655-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of automated malaria diagnosis using the Sysmex XN-30 analyser in a clinical setting

Abstract: BackgroundEarly and accurate diagnosis of malaria is a critical aspect of efforts to control the disease, and several diagnostic tools are available. Microscopic assessment of a peripheral blood smear enables direct visualization of parasites in infected red blood cells and is the clinical diagnostic gold standard. However, it is subjective and requires a high level of skill. Numerous indirect detection methods are in use, but are not ideal since surrogate markers of infection are measured. This study describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 30 publications
(38 reference statements)
2
49
0
1
Order By: Relevance
“…XN-30 had an equal or higher sensitivity than HRP-2 and pLDH respectively, and a higher specificity than both for microscopy-confirmed malaria. Our results are in line with results from a recently published retrospective study on the performance of the XN-30 from South Africa [15]. The accuracy of malaria microscopy (LOD 24 p/μL) in the current study is far above the accuracy of microscopy under field conditions, which is estimated at 50–100 p/μL [16].…”
Section: Discussionsupporting
confidence: 91%
“…XN-30 had an equal or higher sensitivity than HRP-2 and pLDH respectively, and a higher specificity than both for microscopy-confirmed malaria. Our results are in line with results from a recently published retrospective study on the performance of the XN-30 from South Africa [15]. The accuracy of malaria microscopy (LOD 24 p/μL) in the current study is far above the accuracy of microscopy under field conditions, which is estimated at 50–100 p/μL [16].…”
Section: Discussionsupporting
confidence: 91%
“…The search for alternative diagnostic methods for the detection and quantification of Plasmodium infections is ongoing. Automated hematology analyzers can offer fast, sensitive and cost-effective assessments of all suspected malaria infections, as they reduce analytical time and improve accuracy [9][10][11] . The automated hematology analyzer XN-31 prototype (XN-31p) (Sysmex, Japan) is a novel analyzer model that has been optimized to detect Plasmodium-infected red blood cells (iRBCs) circulating in human blood using a combination of optical fluorescence techniques, flow cytometry and laser-optical recognition by a violet semiconductor 405 nm laser beam.…”
mentioning
confidence: 99%
“…Therefore, blood samples from IDA patients would be required for more direct evidence in further analyses. In addition, two recent studies reported that the XN-30 analyser is available for the study of clinical malaria 25,26 . The XN-30 system can evaluate iRBCs, as well as haematological parameters, in approximately 1 min without the requirement for technical expertise 14 .…”
Section: Discussionmentioning
confidence: 99%